# Answer to Question #42281 in Calculus for shasha

Question #42281

Find the inverse of the function.

f(x) = 6x3 - 3

f(x) = 6x3 - 3

Expert's answer

To find the inverse function we should express the x from this expression

So we get

f(x)=6x

f(x)+3=6x

x=((f(x)+3)/6)

f

So we get

f(x)=6x

^{3}-3f(x)+3=6x

^{3}x^{3}=(f(x)+3)/6x=((f(x)+3)/6)

^{1/3}Therefore we getf

^{-1}(y)=((y+3)/6)^{1/3}Need a fast expert's response?

Submit orderand get a quick answer at the best price

for any assignment or question with DETAILED EXPLANATIONS!

## Comments

## Leave a comment